2015
DOI: 10.1108/ijcst-05-2013-0056
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting textile display with floats for electronics covering

Abstract: Purpose – Flexible light-emitting textile display is designed with floats for electronic elements covering and electronic contacts insulation what at the same time provides an opportunity to develop aesthetic design of the display in the single piece construction of material. The paper aims to discuss these issues. Design/methodology/approach – Display consists of interwoven electrically conductive yarns, non-conductive yarns and SMD LED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…When greater complexity is required, electronic-circuit design becomes relevant. Our survey found 15 sources putting focus primarily on electrical signalling [13,23,24,38,44,45,65,67,69,85,86,92,93,114,132] and 15 other sources in which the signalling or wiring plays a major role [3,6,37,70,72,73,82,83,94,95,97,111,115,133,134]. Simple weave [23, 24, 65, 67, 70, 134] [82, 93, 94, 111, 132, 133] F-photodetector [16] F-temperature [16] Temperature and humidity [70] EL wire [56,121] LEDs [16] Capacitive yarn [16,50] PCB [132,133] F-biosensor [16] Optical fbre [42,98,105] Plate capacitor [129] Pressure sensor [16,…”
Section: Electrical Signallingmentioning
confidence: 99%
See 3 more Smart Citations
“…When greater complexity is required, electronic-circuit design becomes relevant. Our survey found 15 sources putting focus primarily on electrical signalling [13,23,24,38,44,45,65,67,69,85,86,92,93,114,132] and 15 other sources in which the signalling or wiring plays a major role [3,6,37,70,72,73,82,83,94,95,97,111,115,133,134]. Simple weave [23, 24, 65, 67, 70, 134] [82, 93, 94, 111, 132, 133] F-photodetector [16] F-temperature [16] Temperature and humidity [70] EL wire [56,121] LEDs [16] Capacitive yarn [16,50] PCB [132,133] F-biosensor [16] Optical fbre [42,98,105] Plate capacitor [129] Pressure sensor [16,…”
Section: Electrical Signallingmentioning
confidence: 99%
“…To create a structure more amenable to textiles, some work has used natural materials -for instance, spinning strands of steel and cotton together [70,94,132,134]. Noninsulated tinsel, consisting of thin strips of copper foil wrapped around a core of plastic fbres [93,94,111], is similar to a copperpolyamide-fbre blend sometimes used [85] and to the silver blends reported upon [73]. Related to these is Jacquard yarn, created by surrounding several strands of thin insulated copper with a twisted or braided silk yarn, with a yarn layer optionally on top [95].…”
Section: Electrical Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Package dies and more specifically LEDs can be also integrated via weaving. In particular, Parvoka et al reported a specific weaving method able to integrate and hide the LED into the textile and this aspect is interesting to improve the aesthetics of the product (Figure 3a) [55,56].…”
Section: Led Devicesmentioning
confidence: 99%